A rapid assessment of litter magnitudes and impacts along the Torre Guaceto marine protected area (Brindisi, Italy). (December 2021) - Rizzo, Angela; Rangel-Buitrago, Nelson; Impedovo, Angelita; Mastronuzzi, Giuseppe; Scardino, Giovanni; Scicchitano, Giovanni
Abstract: This study focuses on assessing litter magnitudes along the Torre Guaceto Marine Protected Area (Brindisi, Italy). Collected litter was grouped into twenty different types and classified into four litter typologies according to the Guidance on Monitoring of Marine Litter in European Seas. All data were analyzed using an index-based approach that allowed the classification of a coastal stretch in terms of cleanliness, and presence of plastics as well hazardous items. The average litter abundance in the study area was 0.5 items/m 2, being plastics the most common litter item. Hazardous litter items were found along the study area, reaching 21.3% of the total collected items. The application of environmental indices allowed to define the study area with a "moderate cleanliness" and a "moderate" presence of hazardous litter items. Sampled litter typologies and related magnitudes suggest a combination of sources that mainly include direct activities on the nearby coastal zones and river basins (dumping). Highlights: The average litter abundance was 0.47 items/m 2 . 20 different litter types under 4 litter typologies. Plastics were the most common item. Moderate cleanliness with a moderate presence of hazardous litter items. Litter derived mainly from four sources through beach and nearby activities.